There is a need for a paradigm shift in laparoscopic surgical training: results of a nationwide survey among teaching hospitals in Switzerland - Karolina Wczysla; Moritz Sparn; Bruno Schmied; Dieter Hahnloser; Stephan Bischofberger (BMC Medical Education, 2024)
Abstract Background Surgical training curricula have changed little over the past decades. Current advances in surgical techniques, especially in minimally invasive surgery, as well as the rapidly changing socioeconomic environment pose a major challenge for the training of young surgeons. The aim of this survey was to provide a representative overview of the surgical training landscape in Switzerland focusing on laparoscopic surgical training: How do department chairs of teaching hospitals deal with the above challenges, and what should a future training curriculum look like? Methods This is a prospective, questionnaire-based, cross-sectional study among the heads of departments of all certified surgical teaching hospitals in Switzerland. Results The overall response rate was 56% (48/86) and 86% (19/22) for tertiary centers. Two-thirds of the centers (32) organize themselves in training networks. Laparoscopic training courses are offered in 25 (52%) hospitals, mainly in tertiary centers. Self-training opportunities exist in 40 (83%) hospitals. In addition to commercial (27) and self-built (7) box trainers, high-fidelity trainers are available in 16 (33%) hospitals. A mandatory training curriculum exists in 7 (15%) facilities, and a training assessment is performed in 15 (31%) institutions. Thirty-two (65%) heads of departments indicated that residents have sufficient practical exposure in the operating room, but the ability to work independently with obtaining the specialist title is seen critically (71%). They state that the surgical catalog does not adequately reflect the manual skills of the resident (64%). The desire is for training to be restructured from a numbers-based to a performance-based curriculum (53%) and for tools to assess residents' manual skills (56%) to be introduced. Conclusions Department chairs stated that the existing curriculum in Switzerland does not meet the requirements of a modern training curriculum. This study highlights the need to create an improved, competency-based curriculum that ensures the training of a new generation of surgeons, taking into account the growing evidence of the effectiveness of state-of-the-art training modalities such as simulation or proficiency-based training.